RECOGNIZING LITERARY FORMULAS OF POP LITERATURE - Tini Mogea (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
This research is to find out the characteristics of Napoleon in Animal Farm. This is a qualitative research project since the data collected is in the form of words rather than numbers. The data were collected in the novel Animal Farm as the primary source. The secondary sources, such as books, documents, and the internet, are used to support the analysis. An objective approach was applied in analyzing the data. The result shows Napoleon possessed certain characters, such as opportunist and dictator, who used hypocrisy, treachery, conspiracy, intimidation, and distortion as his means of achieving his goals. Napoleon uses his power to obtain his ambition. As a man, his ambition to indulge himself is reality, but more ambition is obtained in an unfair way that reflects Napoleon's experience of only destroying other animals. He uses his strength or his power to intimidate or hurt those who are weaker. Four pigs are killed on Napoleon’s order. Three hens were executed, as were a goose and some sheep.